Adaptation of the Era of Disruption in the Agricultural Sector to Realize the Welfare of Farmer Families (Universitas Negeri Semarang, 2020)
The Industrial Revolution forced a shift in all aspects of culture and economy. When the Revolution took place society turned from human power to mechanical power. The dynamic development of the flow of society has made very significant changes, so that it has come to an era where digital miracles seem very amazing. In this era of disruption, development in the agricultural sector underwent strategic environmental changes. This environmental change urges a new perspective for agricultural sector actors to find a new innovation developed for the welfare of farming families. The development of inclusive and sustainable agribusiness is a solution in the agricultural sector in this era of disruption but still requires basic adaptation and adjustment. This paper aims to explore policies, challenges and changes that occur in the agricultural sector in this era of disruption. This scientific article uses a descriptive type of research by using data collection sourced from secondary data. This data was collected based on a literature study conducted by reading, citing information from books, theses, official internet sites, and documents owned by the institution.